Improved Sliding-Mode Vector Control Strategy Combined With Extended Reactive Power for MMC Under Unbalanced Grid Condition - Guan, Tianyi; Zhao, Xin; Zheng, Wenjing; Liu, Hu; Liu, Yao; Sun, Qiuye (Frontiers in Energy Research, 2022)
Proportional–integral vector control (PIVC) has been proposed as an effective control strategy for modular multi-level converter (MMC) under balanced grid conditions. However, the PIVC using traditional power theory has unsatisfactory performances under unbalanced grid conditions, which cannot maintain the AC current sinusoidal while eliminating the twice grid-frequency ripples in active and reactive power. Therefore, an improved sliding-mode vector control (ISMVC) strategy combined with the extended reactive power (ERP) for MMC-based DC power system is proposed in this paper, which can cope with the problems above and work effectively under both balanced and unbalanced grid conditions. Furthermore, the proposed ISMVC shows better dynamic response and robustness than PI and conventional sliding-mode control (SMC) due to the novel design of sliding surface and reaching law. Comparative simulation experiments of the ISMVC and PIVC using the traditional and extended reactive power for MMC are conducted to verify the validity and superiority of the proposed control strategy under different grid conditions.